High expression of CXCR4 and stem cell markers in a monocrotaline and chronic hypoxia-induced rat model of pulmonary arterial hypertension - Zhang, Tingting (Exp Ther Med, 2018)
Pulmonary arterial hypertension (PAH) is a severe and fatal clinical syndrome. C-X-C chemokine receptor type 4 (CXCR4) is known to serve a key role in recruiting mesenchymal stem cells (MSCs) from the bone marrow. In the present study, a rat model of PAH induced by 5 weeks of chronic hypoxia and treatment with a single injection of monocrotaline (60 mg/kg) was used to investigate the involvement of CXCR4 in PAH. Successful establishment of the PAH model was confirmed by significant differences between the PAH and control groups in right ventricular systolic pressure, Fulton index, wall thickness, vascular occlusion score determined by immunohistochemical staining and the expression of inflammatory markers measured by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The expression of CXCR4 and other stem cell markers were compared in the PAH and control groups. RT-qPCR showed that the expression of CXCR4, SCF, c-Kit, and CD29, which are expressed in MSCs, was significantly higher in the PAH group. Immunohistochemical staining also showed that the numbers of CXCR4-, c-Kit- and CD90-positive cells were significantly higher in the PAH group. These results suggest that CXCR4 is involved in the pathogenesis of PAH and that stem cells may serve an important role in pulmonary vascular remodeling.